Facility and Asset Resource Support and Physical Fitness (EUROFIT) in Primary Schoolchildren: A Sex-Stratified Urban–Rural Comparison - Fadhli, Nurrul Riyad; Saputro, Yulianto Dwi; Yudasmara, Dona Sandy; Taufik, Taufik; Hariadi, Imam; Winarno, Mashuri Eko; Aji, Galih Purnomo; Yanto, Nanda Dwi; Putra, Aditya Diana (Physical Education, Health and Recreation Study Program, Universitas Insan Budi Utomo, Indonesia, 2025)
Individual factors and school environments shape the physical fitness of elementary school students, yet comparative evidence across urban–rural contexts by gender and facility support remains limited. This study examined (1) gender-specific differences in EUROFIT performance between urban and rural schools and (2) the association between school facility support and assets (SEFEI) with students’ fitness. A cross-sectional design involved grade 4–6 students (n = 135; ages 9–12) from one urban and one rural school. Fitness was assessed using the complete EUROFIT battery, while the SEFEI index (0–7) captured availability of space, equipment, personnel, and scheduled activities. Analyses used descriptive statistics, group comparisons, and ANCOVA controlling for age and BMI. Results showed boys scored higher than girls on total EUROFIT and strength–speed components, particularly in the bent-arm hang and 10 × 5 m shuttle run. Urban–rural differences were not significant. Urban schools had higher SEFEI scores (+68%) and slightly better fitness outcomes. BMI was a significant covariate, and no sex-by-location interaction emerged. Overall, gender differences were more influential than location, and positive trends between SEFEI and EUROFIT highlight the need to improve facility access and structured physical activity programs in low-resource schools.